Dynamical behavior of a stochastic SICR rumor model incorporating media coverage - Yue, Xuefeng; Huo, Liangan (Frontiers in Physics, 2022)
Rumor propagation in the new media era poses a huge threat to maintaining the normal order of social life. In this context, a stochastic SICR rumor model incorporating media coverage is proposed. Firstly, the existence of the unique global positive solution is obtained. Secondly, sufficient conditions for extinction are constructed on the spread of rumors based on the Lyapunov function methods and the Khasminskii’s theory. Finally, the theoretical analysis is verified through numerical simulations.